PENGARUH HARGA DAN KUALITAS LAYANAN TERHADAP MINAT BELI KONSUMEN PADA PRODUK BUAH LOKAL DI RUMAH BUAH BUMI SERPONG DAMAI TANGERANG SELATAN - Wawan Supriyatna (PIKTORIAL : Journal of Humanities, 2019)
ABSTRACT This study was to analyze the effect of price, and service quality on consumer buying interest in Local Fruits in the Buah Serpong Damai store. This research uses quantitative and qualitative methods. Data was collected by questionnaire and interview techniques. Respondents in this study were 100 people who met one of the five criteria; initiator (initiator), influencer (influencer), interest in buying (interest), buyers (buyers), users (users) of Local Fruit products in the fruit shop of Bumi Serpong Damai. Eight hypotheses were formulated and tested using Regression Analysis. While qualitative analysis is taken from the interpretation of data by giving information and explanation. The results showed that price and service quality had a significant relationship with consumer buying interest. Prices also have a higher influence on consumer buying interest than service quality. Variations in purchasing decisions are explained by variable prices and service quality of 58.2% while the remaining 41.8% is explained by variables or other aspects outside the model. Keywords: Price, Service Quality, Consumer Buying Interest